Research on a new process of reconstituted landess goose steak - Saisai Zhang; Hanrui Wang; SiYuan Li; Junjie Zhang; Linwu Zhuang; Shengfu Li (Food Chemistry: X)
The primary product currently sold from Anser cygnoides is foie gras, with limited research conducted on the processing of Anser cygnoides meat, which consequently restricts its added value. Therefore, the objective of this research is to develop a processing technique for reconstituted goose cutlets using Anser cygnoides meat as the main ingredient, aiming for a compact structure and intact shape after frying. The study examined the effects of compound enzyme quantity, tumbling duration, and molding time on the quality of the reconstituted goose cutlets, utilizing bonding strength, cooking loss rate, color, chewability, adhesiveness, and sensory evaluation as key metrics. Through single-factor and response surface tests, the optimal process parameters were determined as follows: a compound enzyme addition of 3.5 %, a tumbling time of 4 h, and a forming time of 10 h. Under these conditions, the bonding strength measured 34.950 g/cm2, and the reconstituted goose cutlet exhibited strong cohesion while maintaining its shape after frying.